Penerapan Maqasid al-Syariah dalam Pembangunan Model Kepemimpinan Wanita di Malaysia: The Application of Maqasid al-Shariah in the Development of Women’s Leadership Model in Malaysia - Atriza Umar; Hamidah Mat (RABBANICA - Journal of Revealed Knowledge, 2024)
Women’s involvement in the highest leadership positions in Malaysia remains low. Various parties have made multiple efforts to enhance women’s empowerment through opportunities in national leadership. This study examines the relevance of the theory of Maqasid al-Shariah as a foundation for developing a leadership model for women in Malaysia. Maqasid al-Shariah’s theory, which outlines Islamic law’s objectives, offers relevant principles to shape an inclusive leadership model. This qualitative study employs in-depth interviews with experts in Syariah and leadership. The hypothesis assumes that implementing an inclusive leadership model aligned with the principles of Maqasid al-Shariah results in greater social well-being and promotes gender equality in national leadership. The findings of this study provide valuable insights for designers of the women’s leadership model, policymakers, political leaders, and other stakeholders in their efforts to achieve gender equality and social justice in national leadership. Tahap keterlibatan wanita dalam kepimpinan tertinggi negara Malaysia masih berada di tahap yang rendah. Pelbagai usaha dari pelbagai pihak dijalankan demi meningkatkan pemberdayaan wanita menerusi ruang kepimpinan negara. Kajian ini bertujuan mengkaji relevansi teori Maqasid al-Syariah sebagai landasan pembangunan Model Kepemimpinan Negara Malaysia bagi Wanita. Teori Maqasid al-Syariah yang merumuskan objektif-objektif pensyariatan hukum syarak menawarkan prinsip-prinsip yang relevan untuk membentuk model kepemimpinan yang inklusif. Kajian kualitatif ini menggunakan kaedah temubual tidak berstruktur bersama pakar-pakar dalam bidang syariah dan kepimpinan. Hipotesis kajian ini mengandaikan bahawa implementasi model kepemimpinan yang inklusif, sejajar dengan prinsip-prinsip Maqasid al-Syariah, akan menghasilkan kesejahteraan sosial yang lebih besar dan mempromosikan kesetaraan gender dalam kepemimpinan negara. Kesimpulan dari kajian ini dijangka dapat memberikan pandangan yang berharga designers of the women’s leadership model, pembuat dasar, pemimpin politik, dan pihak berkepentingan lain dalam usaha mereka untuk mencapai kesetaraan gender dan keadilan sosial dalam kepemimpinan negara.